EXTERNAL FISCAL CONTROL FROM THE COMPLEMENTARITY OF THE CITIZEN CONTROL OF PUBLIC POLICIES - Castillo Liendo, Yrayma de las Nieves (2023)
The control of public policies seeks to verify if the real conditions of their materialization are in accordance with the established criteria. The article analyzes the external fiscal control related to the complementarity that citizen control provides in the surveillance of public policies. For this, a documentary research with bibliographic design was carried out. The conclusions deal with the importance of complementarity as a means to ensure the correct execution of public policies, consolidate the transparency of public management and guarantee the compliance with Human Rights.